Rasio Monosit-High Density Lipoprotein (RMH) sebagai prediktor independen kejadian kardiovaskular mayor selama rawat inap pada pasien Infark Miokard Akut (IMA) yang menjalani intervensi koroner perkutan di RSUP Sanglah, Bali, Indonesia - Ni Made Dharma Laksmi; I Gusti Ngurah Putra Gunadhi; Hendy Wirawan; Rani Paramitha Iswari Maliawan (Intisari Sains Medis, 2020)
Background: Several inflammatory cell markers have been addressed in recent studies and one of them is the Ratio of Monocyte-High Density Lipoprotein (RMH) as a new predictor and prognostic indicator of cardiovascular disease. There is, however, still little evidence to relate RMH parameters to the severity of coronary lesions in patients with Acute Myocardial Infarction (AMI). In order to determine whether RMH was a predictor of Major Cardiovascular Events (MACE) in AMI patients who underwent percutaneous coronary intervention at the Sanglah General Hospital during hospitalization, this analysis was carried out.Methods: This study was an observational study design with a cohort study approach. The selection of study subjects was carried out by consecutive sampling, with a total of 60 patients. AMI patients who underwent percutaneous coronary intervention were included in the affordable population and met the inclusion and exclusion criteria during the study period. Data were analyzed with SPSS version 23 for Windows.Results: An independent measure of the occurrence of MACE during hospitalization in AMI patients is a high RMH value (RR = 1.459; p = 0.046; 95 percent CI = 1.028–25.366). In addition, it was found that independent predictors of mortality were smoking (RR = 1.555; p = 0.039; 95% CI = 1.131-116.058), diabetes mellitus type 2 (DM-2) (RR = 1.507; p = 0.036; 95% CI = 1.133-45,368) and high TIMI (RR = 1.512; p = 0.026; 95% CI = 1.268-43.772).Conclusion: In acute myocardial infarction patients, the high RMH value is an independent indicator of major cardiovascular events during hospitalization. Other variables such as diabetes mellitus, smoking, and the TIMI score were also found as predictors of major cardiovascular events during treatment in patients with acute myocardial infarction.  Latar Belakang: Berbagai studi terakhir, banyak membahas tentang penanda dari sel inflamasi, dan salah satunya Rasio Monosit-High Density Lipoprotein (RMH) sebagai prediktor baru dan indikator prognosis dari penyakit kardiovaskular. Namun masih sedikit data yang menghubungkan parameter RMH terhadap derajat keparahan lesi koroner pada pasien Infark Miokard Akut (IMA). Studi ini dilakukan untuk mengetahui apakah RMH merupakan prediktor terhadap Kejadian Karviovaskular Major (KKM) pada pasien IMA yang menjalani intervensi koroner perkutan selama rawat inap di Rumah Sakit Umum Pusat Sanglah.Metode: Penelitian ini merupakan rancang studi observasional dengan pendekatan studi kohort. Pemilihan subjek penelitian dilakukan secara consecutive sampling dengan total 60 pasien. Pasien IMA yang menjalani intervensi koroner perkutan yang masuk populasi terjangkau dan memenuhi kriteria inklusi maupun eksklusi selama periode penelitian. Data dianalisis dengan SPSS versi 23 untuk Windows.Hasil: Nilai RMH yang tinggi (RR=1,459; p=0,046; 95% IK=1,028–25,366) merupakan prediktor independen terhadap kejadian KKM selama rawat inap pada pasien IMA. Selain itu didapatkan bahwa merokok (RR=1,555; p=0,039; 95% IK=1,131-116,058), Diabetes Mellitus Tipe 2 (DM-2) (RR=1,507; p=0,036; 95% IK=1,133-45,368), dan TIMI yang tinggi (RR=1,512; p=0,026; 95% IK=1,268-43,772) merupakan prediktor independen terhadap mortalitas.Kesimpulan: Nilai RMH yang tinggi merupakan prediktor indedepnden terhadap kejadian kardiovaskular mayor selama rawat inap pada pasien infark miokard akut. Didapatkan juga faktor lain seperti diabetes mellitus, merokok, dan skor TIMI sebagai prediktor terhadap kejadian kardiovaskular mayor saat perawatan pada pasien infark miokard akut.